HOW TO BUILD ISLAMIC FINANCIAL INDUSTRY - Mohammad Haikal (SHIBGHAH: Journal of Muslim Societies, 2019)
The development of Islamic finance globally is increasingly widespread and attracts attention not only in Muslim countries but also in various non-Muslim countries. Indonesia as one of the largest Muslim countries has a great opportunity to become a major player by preparing facilities and infrastructure that are able to answer the needs of the industry. This study examines the factors that accelerate Islamic economic development by scrutinizing the advantages that have been carried out by other countries. Research is conducted based on the study of literature as well as various reports from varying entities. Research results show there are a number of important factors, namely business transformation, IT infrastructure, talent, and standardization and harmonization. The implication of this study is that any party which wants to prepare for the development of the Islamic financial industry should concentrate on these area in order to accelerate the economic growth.